Full Efficiency Recovery in Hole-Transporting Layer-Free Perovskite Solar Cells With Free-Standing Dry-Carbon Top-Contacts - Valastro, Salvatore; Smecca, Emanuele; Sanzaro, Salvatore; Deretzis, Ioannis; La Magna, Antonino; Numata, Youhei; Jena, Ajay Kumar; Miyasaka, Tsutomu; Gagliano, Antonio; Alberti, Alessandra (Frontiers in Chemistry, 2020)
Carbon-based top-electrodes for Hole-Transporting-Layer-free Perovskite Solar Cells (PSCs) were made by hot-press (HP) transfer of a free-standing Carbon-Aluminum foil at 100°C and pressure of 0.1MPa on a Methylammonium Lead Iodide (MAPbI3) layer. Under these conditions, the perovskite surface is preserved from interaction with the solvent. HP-PSCs have been systematically compared, along a time-scale of 90 days, to reference cells having Carbon-based top electrodes deposited by doctor blading (DB). We found that all the photovoltaic parameters recorded in HP-PSCs during time under ambient conditions settle on values systematically higher than those measured in the reference DB-PSCs, with efficiency stabilized at around 6% within the first few measurements. On the opposite side, in DB-PSCs, a long-lasting (~14 days) degrading transient of the performances is observed with a loss of efficiency from the initial ~8% to ~3%. Moreover, in the HP-PSCs a systematic day-by-day recovery of the efficiency after operation is observed (Δ~2%) by leaving the cell under open circuit, nitrogen environment and dark conditions. Noteworthily, a full recovery of all the parameters is observed at the end of the experiment while DB-PSC only shows a partial recovery at the same conditions. Hence, the complete release of solvent from the carbon contact before an interface is established with the perovskite layer offers a definite advantage through the long period of operation in preventing irreversible degradation. Our findings indeed highlight the crucial role of the interfaces in the performance restoring, especially under nitrogen atmosphere.